2022
DOI: 10.3389/fevo.2022.846975
|View full text |Cite
|
Sign up to set email alerts
|

Riverine Barriers as Obstacles to Dispersal in Amazonian Birds

Abstract: Amazonian rivers represent known barriers for avian dispersal, reducing gene flow and enhancing differentiation. Despite the importance of rivers in the avian evolutionary process, we have made only minor advances in understanding the limitations imposed by rivers on flying birds. To fill that gap, we conducted dispersal-challenge experiments over water, assessing the flying capabilities of 84 tropical bird species of 22 different avian families. We mist-netted and released 484 birds from a stationary boat on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 72 publications
1
17
0
1
Order By: Relevance
“…This metric is typically based either on morphology, such as wing shape (Claramunt, 2021; Kipp, 1959), or on ecological traits thought to predispose species to dispersive lifestyles, such as foraging ecology and diet (Burney & Brumfield, 2009; Miller et al, 2021). Recently, researchers have also conducted dispersal challenge experiments to measure an individual's relative flying ability (Moore et al, 2008; Naka et al, 2022). Naka et al (2022) found no correlation in these experiments between flight distance and riverine island specialization, suggesting that wing shape, rather than ecological preference, better explains the capacity of birds to cross an open gap of water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This metric is typically based either on morphology, such as wing shape (Claramunt, 2021; Kipp, 1959), or on ecological traits thought to predispose species to dispersive lifestyles, such as foraging ecology and diet (Burney & Brumfield, 2009; Miller et al, 2021). Recently, researchers have also conducted dispersal challenge experiments to measure an individual's relative flying ability (Moore et al, 2008; Naka et al, 2022). Naka et al (2022) found no correlation in these experiments between flight distance and riverine island specialization, suggesting that wing shape, rather than ecological preference, better explains the capacity of birds to cross an open gap of water.…”
Section: Discussionmentioning
confidence: 99%
“…The Amazon Basin has high avian species richness (Jenkins et al, 2013; Wallace, 1878), long‐term evolutionary persistence (Bicudo et al, 2019; Harvey et al, 2017b), a wide diversity of habitat types (Tuomisto et al, 1995; Tuomisto et al, 2019), and species with a diversity of habitat preferences and specializations (e.g., Álvarez Alonso et al, 2013; Kratter, 1997; Rosenberg, 1990; Terborgh, 1985). Additionally, experimental dispersal challenges over water are now available for some Neotropical birds (Moore et al, 2008; Naka et al, 2022). Claramunt et al (2022) found that wing morphology was a significant predictor of overwater flight ability and Weeks et al (2022) found a significant association between flight ability and natal dispersal distance in a phylogenetically diverse set of 114 bird species, supporting wing measurements from research specimens as a proxy for dispersal.…”
Section: Introductionmentioning
confidence: 99%
“…Data on dispersal capacity, however, indicate that C. bicolor is a better disperser than both M. propinqua and S. napensis (Naka et al, 2022). In dispersal challenge experiments conducted on the Rio Branco, C. bicolorcolour managed to safely cross river gaps in all trials (10:0), whereas S. napensis failed in 25% and M. propinqua in more than 50% of the trials.…”
Section: Discussionmentioning
confidence: 99%
“…In these habitats, species need larger foraging areas and thus enhanced mobility in order to obtain sufficient resources. Finally, even in productive tropical forests, ground‐foraging species may show higher levels of mobility than species that forage on understory vegetation (Claramunt et al, 2022 ; Naka et al, 2022 ). These factors may complicate the relationship between foraging behavior and dispersal distances.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its role in determining the efficiency of movements through space, flight efficiency can also influence other aspects of birds' biology. For example, flight efficiency has a strong influence on the species' ability to cross habitat gaps and move across fragmented landscapes (Claramunt et al, 2012(Claramunt et al, , 2022Hartfelder et al, 2020;Ibarra-Macias et al, 2011;Naka et al, 2022). Flight efficiency may also be linked to foraging behavior and, by extension, to diet and habitat (Norberg, 1990;Rayner, 1988;Sherry, 2016).…”
Section: Discussionmentioning
confidence: 99%